2011
DOI: 10.1016/j.micres.2010.09.004
|View full text |Cite
|
Sign up to set email alerts
|

Gene silencing of the Lentinula edodes lcc1 gene by expression of a homologous inverted repeat sequence

Abstract: Lentinula edodes is one of the most important edible mushrooms, but no method for analyzing its molecular genetics has yet been established. RNA interference (RNAi) is a mechanism that inhibits expression of specific genes at the post-transcriptional stage and has been used to analyze the genetics of several fungal species. RNAi was used to examine the expression of the laccase (EC 1.10.3.2) gene lcc1 of L. edodes, which encodes a lignin-degrading enzyme. Vector pChG'-ivrL1 that expressed a 40 bp homologous in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
40
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 45 publications
(40 citation statements)
references
References 40 publications
0
40
0
Order By: Relevance
“…2). RNA interference tools are available in Lentinula edodes (40,73), and TILLING, a method for screening mutants that have a mutation in a target gene (74), will be applicable for breeding. Gene expression for wood decay, biofilm formation in sawdust, medium cultivation, and fruiting body primordia in Lentinula edodes has been reported.…”
Section: Resultsmentioning
confidence: 99%
“…2). RNA interference tools are available in Lentinula edodes (40,73), and TILLING, a method for screening mutants that have a mutation in a target gene (74), will be applicable for breeding. Gene expression for wood decay, biofilm formation in sawdust, medium cultivation, and fruiting body primordia in Lentinula edodes has been reported.…”
Section: Resultsmentioning
confidence: 99%
“…In N. crassa, it has been demonstrated that hpRNA gene silencing is more efficient and stable compared to quelling induced by promoterless transgenes (Goldoni et al, 2004;Romano and Macino, 1992). Within the developed vectors for this application, the pSilent-1 vector enables high performance in RNA silencing (Nakayashiki et al, 2005;Shafran et al, 2008). pSilent-1 has a hygromycin resistance cassette and a transcriptional unit for expressing RNA hairpin with a spacer consisting of an intron of cutinase from Magnaporthe oryzae (Nakayashiki et al, 2005).…”
Section: Strategies and Applications Of Rnai For Research On Functionmentioning
confidence: 99%
“…RNAi enables researchers the ability to attenuate the expression of specific genes at different levels while keeping the organism viable even when applied to genes vital for cell survival (Nakayashiki et al, 2005). In addition, RNAi enables the silencing of a complete gene family, simultaneously (Salame et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations